The Effectiveness of Reading Spinning Wheel Learning Media on Initial Reading Ability in Elementary Schools - Ningrum, Zahra Puspita; Kaltsum, Honest Ummi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to know the level of students' initial reading comprehen-sion before and after using spinning wheel learning media and to test the ef-fectiveness of reading spinning wheel media on initial reading ability. Methodology: The research method used is quantitative Pre-Experimental with One-Group Pretest-Posttest Design. The data collection instruments are pretest and post-test. The subject of this study is grade 1 of SDN 02 Pasekan Ambarawa, with a total of 37 students. Results: The research results show that the average difference between the pretest and the posttest was 14.46, meaning there was a significant increase in reading comprehension. The N-gain result of the percent of pretest and posttest data is 57.999%, which means that using the reading spinning wheel media is quite effective. The results of the T-test showed a significance result of 0.000 < 0.05, then H0 was rejected, and Ha was accepted. This refers to the use of reading spinning wheel media on the initial reading ability of grade 1 students of SDN 02 Pasekan Ambarawa has been tested to be effective. Applications/Originality/Value: The authenticity of this study is that there are pockets and letter cards to form a syllable, word, or sentence on the media. The pragmatic implication of this study is that innovative and interactive reading spinning wheel media can engage students and create a fun reading learning atmosphere in terms of initial reading skills.